1990
DOI: 10.1172/jci114943
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic acid modulates rat Ito cell proliferation, collagen, and transforming growth factor beta production.

Abstract: Recent studies suggest that vitamin A plays an inhibitory role with respect to "activation" of the hepatic Ito cell, a likely effector of hepatic fibrogenesis. Ito cell "activation" during fibrogenesis is characterized by a decrease in intracellular vitamin A and an increase in cellular proliferation and collagen production. To explore the hypothesis that retinoids have the capacity to diminish Ito cell activation, cultured Ito cells were exposed to retinoic acid and its effects assessed on three key features:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
78
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(80 citation statements)
references
References 61 publications
1
78
0
Order By: Relevance
“…44 Several previous A hepatotoxicity. 40 The suppression of stromelysin and colla-studies have shown that both RA and retinol may reduce genase gene promoters by RA 41,42 may partly account for this SC proliferation both in basal conditions, [45][46][47] and following fibrosis-enhancing effect. Previously, we have observed that stimulation with growth factors involved in liver inflammanthe acyclic retinoid used in the current study reduces the tion.…”
Section: Discussionmentioning
confidence: 99%
“…44 Several previous A hepatotoxicity. 40 The suppression of stromelysin and colla-studies have shown that both RA and retinol may reduce genase gene promoters by RA 41,42 may partly account for this SC proliferation both in basal conditions, [45][46][47] and following fibrosis-enhancing effect. Previously, we have observed that stimulation with growth factors involved in liver inflammanthe acyclic retinoid used in the current study reduces the tion.…”
Section: Discussionmentioning
confidence: 99%
“…Retinoic acid signaling is greatly suppressed in HSCs during experimental cholestatic liver fibrosis and correlated with a decrease in the mRNA levels for RXR and retinoic acid receptors (Ohta et al, 1997). Furthermore, retinoic acids have been reported to prevent phenotypic change and proliferation in activated HSCs (Davis et al, 1988;Davis et al, 1990;Pinzani et al, 1992). Although intracellular lipid droplets containing vitamin A disappear by HSC activation, whether or not retinoid loss is directly related to HSC activation is still unclear.…”
Section: Nuclear Receptors and Hscsmentioning
confidence: 99%
“…Activation of HSC is associated with release and metab-produce components of the plasminogen-activating system, olism of endogenous retinyl palmitate to free retinoids includ-suggesting that these cells not only produce MMPs but may ing recently identified retroretinoids, which may be also regulate the activities of those members of the MMP important autrocrine modulators of HSC function. 13,35 The family that require activation by plasmin, e.g., interstitial effect of retinoic acid on uPA and PAI-1 production was as-collagenase and stromelysin. The detection of mRNA for uPA sessed in 14-day cultured HSCs, at which time they are and PAI-1, and the demonstration by zymography of uPA largely depleted of their endogenous retinoids.…”
Section: Effect Of Retinoic Acid On the Plasminogen-activating Sys-mentioning
confidence: 99%